Fetal Ventriculomegaly and Outcomes: About 3 Cases - MAMA, SY; POATY, Henriette; AZONBAKIN, AZANDÉGBÉ SIMON; FAYE, OMAR; GANGBO ÉPSE HOUNDJO, FLORE ARMANDE (My University, 2019)
Introduction: Ventriculomegaly is one of the most common abnormalities detected by prenatal ultrasound. This entity can be associated with brain abnormalities and other malformations. In order to perform a good prenatal counseling, the diagnosis is essential. Objective: Our purpose was to report the management of 3 cases of ventriculomegaly in our practice and underline the benefits of the neuropathologic exam. Methods: We analyzed retrospectively 3 medical files concerning fetus that were diagnosed as having one or two ventricles of >10 mm and a follow up for prenatal diagnosis. Results: All cases were diagnosed between 22 and 27 weeks of gestation by an ultrasound. In a case, the ventriculomegaly evolved rapidly to a hydrocephalus. In two cases, the pregnancy was terminated with medical interruption by the parent’s request. Amniocentesis confirmed the diagnosis of congenital toxoplasmosis in case 2 there were no chromosomal abnormalities after karyotyping. Causes included holoprosencephaly, congenital toxoplasmosis and mesencephalosynapsis. Conclusion: Ultrasonography may detect ventriculomegaly nerverthless in the cases presented, pathology exam was essential to assess the diagnostic. Causes are numerous and prognosis variable. We recommand MRI that is more and more accessible in our regions in the follow up of this entity and neuropathology exam in case of termination of the pregnancy. The establishment of main causes of ventriculomegaly in our regions (infectious causes for example) could help to prevent this outcome in our practice.
Keywords: Fetal Ventriculomegaly; Neuropathology; Prenatal Diagnosis